Influence of Low-Temperature Stress-Relieving Treatment in the Fatigue Life of Components Produced by Laser Powder Bed Fusion in AlSi10Mg - Malcolm António; Rui Fernandes; Joel de Jesus; Luís Borrego; Ricardo Branco; José da Costa; José Ferreira (Applied Sciences)
This study investigates the impact of low-temperature stress-relieving treatment on the fatigue life of AlSi10Mg components produced by Laser Powder Bed Fusion (L-PBF). The research focuses on a bicycle crank arm, comparing its performance in as-built and heat-treated conditions. The heat treatment involved stress-relieving at 250 °C for 2 h, followed by water quenching. The study found that the as-built condition exhibited a supersaturated Si cellular-dendritic microstructure, while the heat-treated condition showed coarsening of β-Mg2Si phases and Si precipitates. This morphological change led to a decrease in hardness and an increase in ductility. Fatigue tests demonstrated that the heat-treated crank arms achieved the target of 100,000 cycles without failure, unlike the as-built samples, which failed prematurely. The fractography analysis identified surface porosity as the primary crack initiation site. The findings suggest that low-temperature stress-relieving treatment can enhance the fatigue performance of L-PBF AlSi10Mg components by reducing residual stresses and improving defect tolerance.